Effects of empathy on the bidirectional relationships between problematic smartphone use and aggression among secondary school students: a moderated network approach - Wu, Wenxia; Zou, Xinyuan; Tang, Qihui; Tao, Yanqiang; Wang, Shujian; Ma, Zijuan; Li, Min; Liu, Gang (Frontiers in Psychiatry, 2024)
Background: Existing literature on the relationship between problematic smartphone use (PSU) and aggression has primarily focused on examining their unidirectional association, with limited attention paid to the bidirectional nature of this relationship, particularly when considering the role of empathy. This study employs a novel moderated network approach to examine the bidirectional relationship between problematic smartphone use and aggression, while also investigating the moderating mechanism of empathy.Methods: A total of 2,469 students (49.1% female, Mean age = 13.83, SD age = 1.48) from 35 junior and senior high schools in Harbin, China, participated in this study.Empathy level, aggressiveness, and PSU symptoms were assessed using the Basic Empathy Scale, the Buss-Warren Aggression Questionnaire, and the Mobile Phone Addiction Index.Results: Analysis revealed that the relationship between PSU and aggression was complex and bidirectional. The strongest association was observed between "hostility" and "withdrawal/escape". In addition, "anger" had the highest ExpectedInfluence (EI) in both affective and cognitive moderate network models. An important discovery was also made regarding the conditional effect of "productive loss" and "physical aggression" across different levels of affective empathy. Specifically, at lower levels of affective empathy, a positive bidirectional relationship was found between "productive loss" and "physical aggression". However, this relationship turned negative and bidirectional at higher levels of affective empathy.The findings contribute to a more comprehensive understanding of the complex dynamics between PSU and aggression and highlight the need for targeted interventions that promote affective empathy to mitigate the negative consequences of excessive smartphone use.